2005
DOI: 10.1111/j.1365-2567.2005.02163.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of long‐term tumour‐specific T‐cell memory by residual dormant tumour cells

Abstract: Summary LacZ (Gal)‐reactive immune cells were transferred into athymic nu/nu mice inoculated with Gal‐expressing syngeneic tumour cells (ESbL‐Gal) in order to study tumour‐protective T‐cell memory. This transfer prevented tumour outgrowth in recipients and resulted in the persistence of a high frequency of Gal‐specific CD8+ T cells in the bone marrow and spleen. In contrast, such Ag‐specific memory CD8+ T cells were not detectable by peptide–major histocompatibility complex (MHC) multimer staining in animals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 51 publications
8
51
0
2
Order By: Relevance
“…This could be explained with the formation of a long-lived memory T cell population that preferentially resides in the bone marrow but only after treatment with the tumor vaccine. This is consistent with reports by others that CD44 hi CD62L hi CD27 hi memory T cells reside primarily in the bone marrow where they acquire all necessary signals/factors for their survival and proliferation (42)(43)(44). Beside the IL-15, also the CD70/CD27 interactions are important in this maintenance suggesting that the CD27 and IL-15 signals work together to optimize this response (29,39).…”
Section: Discussionsupporting
confidence: 80%
“…This could be explained with the formation of a long-lived memory T cell population that preferentially resides in the bone marrow but only after treatment with the tumor vaccine. This is consistent with reports by others that CD44 hi CD62L hi CD27 hi memory T cells reside primarily in the bone marrow where they acquire all necessary signals/factors for their survival and proliferation (42)(43)(44). Beside the IL-15, also the CD70/CD27 interactions are important in this maintenance suggesting that the CD27 and IL-15 signals work together to optimize this response (29,39).…”
Section: Discussionsupporting
confidence: 80%
“…Preclinical studies show that indolent tumor cells in the bone marrow are the source of antigenic stimulation that could maintain T-cell memory pool (24) to keep indolent tumor cells in check. Cancer vaccines that target tumor blood vessel antigens could also induce and maintain CD8 þ T-cell-dependent tumor dormancy (25).…”
Section: Immunotherapy Is a Promising Approach For Tumor Dormancy Andmentioning
confidence: 99%
“…Studies on different cancers have shown a significant reduction in tumor progression in case of infiltration of the tumor by the T lymphocytes [16,17]. Mouse lymphoma studies have shown that malignant cells are kept at low numbers in the bone marrow owing to persistent antigen and memory T cells that are able to coordinate a CD4 + and CD8 + T cell-mediated response [18]. Loss of MHC class I and other components of class I processing pathway in cancer cells point towards the importance of CD8 + T cells, in particular, in preventing the disease progression [19].The extent of involvement of other T cell subtypes like the T regulatory cells (CD4 + CD25 + Foxp3 + T cells or Treg)) in maintenance of CI equilibrium however remains to be investigated.…”
Section: What Maintains the CI Equilibrium?mentioning
confidence: 99%